2016
DOI: 10.1021/acs.nanolett.6b02213
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation-Based Single-Molecule Fluorescence Assay To Study DNA Supercoil Dynamics

Abstract: DNA supercoiling crucially affects cellular processes such as DNA replication, gene expression, and chromatin organization. However, mechanistic understanding of DNA supercoiling and the related DNA-processing enzymes has remained limited, mainly due to the lack of convenient experimental tools to probe these phenomena. Here, we report a novel high-throughput single-molecule assay for real-time visualization of supercoiled DNA molecules, named ISD (Intercalation-induced Supercoiling of DNA). We use an intercal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(109 citation statements)
references
References 51 publications
9
100
0
Order By: Relevance
“…Defects in duplex DNA can arise from base-pair mismatches 18,25 , damaged 26 or modified bases 27 , locally melted DNA bubbles 28 , a protein introduced kink in the DNA 29 . An elastic rod with a defect that locally decreases the bending rigidity, when subjected to torsional stress, would buckle at the defect 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Defects in duplex DNA can arise from base-pair mismatches 18,25 , damaged 26 or modified bases 27 , locally melted DNA bubbles 28 , a protein introduced kink in the DNA 29 . An elastic rod with a defect that locally decreases the bending rigidity, when subjected to torsional stress, would buckle at the defect 30 .…”
Section: Introductionmentioning
confidence: 99%
“…[7] demonstrated that energy is minimized by the colocalization of plectoneme end-loops and regions of unpaired bases as “tip bubbles.” Ganji et al . [8] used an intercalator based method for creating fluorescent plectonemes and showed a preference for plectoneme pinning at the location of a 10 bp mismatch.…”
mentioning
confidence: 99%
“…On the other hand, superhelical structure, which is a hierarchical structure in which a helix is further folded to produce a more ordered helix, is another higher order and more sophisticated structure from natural creatures, especially in the closed‐circular DNA systems. Superhelical structures also play important roles in a number of biological processes, such as compacting DNA and storing energy for essential biological functions including muscle contraction, metabolism, transcription, molecular chaperons, membrane channels, and chromatin organization . Reported creations of synthetic superhelical fibers were mainly based on the self‐assembly of chiral/achiral molecules or π‐conjugated polymers by carefully adjusting the subtle interplays of various noncovalent interactions .…”
mentioning
confidence: 99%
“…Superhelical structures also play important roles in a number of biological processes, such as compacting DNA and storing energy for essential biological functions including muscle contraction, metabolism, transcription, molecular chaperons, membrane channels, and chromatin organization. [25][26][27][28] Reported creations of synthetic superhelical fibers were mainly based on the self-assembly of chiral/achiral molecules or π-conjugated polymers by carefully adjusting the subtle interplays of various noncovalent interactions. [29][30][31][32] And thus, precise molecular design and complicated synthesis procedure were often required.…”
mentioning
confidence: 99%